Interactive learning media and improving the creativity of Buddhist sunday school students in Tanjung Sari district - Agus Saputra; Dedi Kundana; Hendri Ardianto (Universitas Sebelas Maret, 2025)
This study aims to analyse the influence of interactive learning media on increasing the creativity of Buddhist Sunday School students in Tanjung Sari District. This research departs from the problem of low student activity in discussing, asking questions, and contributing to the learning process. Students tend to be passive because they are less interested in monotonous teaching methods, limited to the use of textbooks as the primary source. This study uses a quantitative approach with a survey method. The research population consisted of all 78 students of the Buddhist Sunday School in Tanjung Sari District. The sample was determined using the saturated sampling technique, so that the entire population was used as respondents. Data collection was conducted using a Likert scale questionnaire that had undergone validity and reliability tests. Data were analysed using simple linear regression to test the influence of independent variables on dependent variables, assisted by SPSS software 24. The results of the study show that there is a positive and significant influence of interactive learning media on increasing student creativity. The results of the study indicate that interactive learning media requires careful planning in order to motivate students to be actively involved. Therefore, Buddhist Sunday School teachers need to adapt the use of interactive media to the needs, characteristics, and level of development of students, as well as create a learning climate that supports participation and freedom of expression. Thus, interactive learning media can be an effective means of encouraging creativity, as long as it is supported by the right learning strategies and good communication skills of teachers.